EXPERIENCE OF USE OF PNEUMOCOCCAL CONJUGATED 7-VALENT VACCINE IN SOME REGIONS OF RUSSIA - A.A. Ruleva; S.M. Kharit; N.F. Snegova; V.P. Vavilova; O.A. Vaiman; V.L. Mamet'eva; E.A. Andreeva; T.A. Vavilova ("Paediatrician" Publishers LLC, 2010)
An experience of immunization with pneumococcal conjugated 7-valent vaccine Prevenar in 234 children under 5 years old with different state of health was analyzed. There were no any severe reactions, postvaccinal complications or local reactions to the vaccine injection. Mild and moderate postvaccinal reactions were detected in 3,4% (n = 8) of children. The vaccine can be used in children under 5 years old.Key words: children, vaccination, pneumococcal conjugated 7-valent vaccine, safety.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(2):119-123)